Simplified bronchiolitis severity score for health care providers - Rudhan, Rachel P.; Biswal, Niranjan (International Journal of Contemporary Pediatrics, 2019)
Background: Bronchiolitis is a viral lower respiratory infection of young infants. It requires monitoring by outpatient health care providers and rarely needs hospitalization. Scoring of severity in community helps in early referral. A simplified bronchiolitis scoring for rural health care providers with no facility for measurement of oxygen saturation (SpO2) and chest X-ray (CXR) is a long-felt need. This study proposes a simplified score. Methods: The proposed bronchiolitis severity score (PSS) has to be validated against the standard bronchiolitis severity score (SSS). The PSS was administered by a physician, nurse and researcher. The reliability was measured by the comportment of internal consistency and inter-observer agreement. Results: The physicians rating of severity by SSS and PSS was similar in 97% of cases. The internal consistency of 0.72 and the kappa index of 0.86 were obtained. The inter-rater agreements between physician, nurse, researcher was 0.94, 0.94 and 0.93 respectively. Conclusions: The PSS is reliable, valid and can be administered by nurses in peripheral health care settings.